Composition and structure of forest communities in a fragmented rural landscape: the Middle Hills of Eastern Nepal - Magraw, K. N. L.; Detling, J. K. (Banko Janakari, 2013)
Rising population and land use intensification in the Middle Hills (1,000-3,000 melevation) of Nepal have resulted in widespread conversion of primary forests,and there is limited understanding of the degree to which conversion affectsplant community composition. This study describes and compares vascularplant communities in four vegetation types in the eastern Middle Hills of Nepal:primary forests, deforested areas, large cardamom (Amomum subulatum)plantations, and conifer plantations. We sampled nested plots in 18 stands andwe analyzed indicators such as species richness and diversity, unique species,stand composition, and structure. Primary forests and conifer plantations hadsignificantly greater species richness than deforested areas and cardamomplantations (P≤0.001). Primary forests exhibited complex structure and contained 229 species, 30% of which were unique to this vegetation type. Deforestedareas contained sparse woody vegetation, many species suited to exposedhabitats, and 178 species. Cardamom plantations contained 174 speciesand were characterized by an Alnus nepalensis overstory (82.4% of stems ≥3.2cm dbh) and A. subulatum in the understory. Conifer plantations were stockedwith Cryptomeria japonica, Pinus wallichiana, or Pinus roxburghii. Of 217species encountered, only 16% were unique to this vegetation type, althoughspecies diversity was comparatively high (Shannon-Wiener index: 3.34). Ourfindings indicate that vegetative composition was influenced by (a) the degreeof disturbance and management and (b) aspect and elevation, and thereforeplant community composition in primary forests is unlikely to be approximatedin other vegetation types or in forests positioned differently on the landscape. DOI: http://dx.doi.org/10.3126/banko.v22i2.9196 Banko Janakari: A Journal of Forestry Information for Nepal Vol. 22, No. 2, 2012 November Page: 11-18 Uploaded date: 12/1/2013